Edukasi Tentang Anemia dan Pemeriksaan Hb pada Ibu Hamil serta Pengobatan pada Masyarakat di Nagari Carocok Anau Kec.Tarusan Kab. Pesisir Selatan - Elmatris Sy; Dessy Arisanti; Almurdi Almurdi; Endrinaldi Endrinaldi; Bobby Indra Utama; Dian Pertiwi; Rauza Sukma Rita; Zelly Dia Rofinda; Hasmiwati Hasmiwati; Aswiyanti Asri; Julizar Nazar; Mohamad Reza (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
The majority of people of Nagari Carocok Anau Kec. Tarusan Kab. Pesisir Selatan worked as a fisherman, farmer, a small number of civil servants and market traders, as well as a housewife. Pregnant women in Nagari Carocok Anau, most of whom are housewives, still do not receive health checks such as haemoglobin (Hb) checks. This activity aims to increase knowledge among the public and health cadres regarding anaemia and Hb examination in pregnant women, as well as treatment. The health of pregnant women is checked by checking blood pressure, Hb and medication. This Hb examination is an effort to minimize abnormalities that can occur in pregnant women and fetuses due to low Hb when the mother is pregnant. The examination results showed that more than half of the pregnant women (71.43%) who attended were in the age range 18 – 35 years. Nearly half (42.86%) of pregnant women had Hb levels below the normal limit (11 mg/dl). For a more valid diagnosis, it is necessary to carry out quantitative analysis from the hospital laboratory so that follow-up can be carried out. Education about anaemia and Hb examinations in pregnant women can increase people's knowledge so that preventive measures can be carried out early. Health checks on the general public (blood pressure, Hb) and treatment were also carried out, it was found that the Hb results were within normal limits.